2000
DOI: 10.1001/jama.283.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Physicians Helping the Underserved

Abstract: In the current health care environment of competition and market forces, concern has arisen that the classic principle of serving disadvantaged persons may not be fulfilled due to pressures from managed care. Reach Out, a $12 million national program of the Robert Wood Johnson Foundation, was developed to recruit leaders from among practicing physicians to organize projects to care for the uninsured and underserved. Physician volunteerism was a key component of all projects. Thirty-nine Reach Out projects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…32 Doctors in the US National Health Service Corps -which places student loan recipients in approved services for the poor or marginalised after graduation -are more likely to stay beyond their 2-year tour of duty if they have higher salaries and greater job satisfaction. 33 In the present study, the relatively low levels of reimbursement for working in the field was rarely mentioned as a barrier by participants; however, this population with their varied careers could afford to carry low-paid work, as it was offset by other work.…”
Section: Box 5 Team Work and Boundariesmentioning
confidence: 99%
“…32 Doctors in the US National Health Service Corps -which places student loan recipients in approved services for the poor or marginalised after graduation -are more likely to stay beyond their 2-year tour of duty if they have higher salaries and greater job satisfaction. 33 In the present study, the relatively low levels of reimbursement for working in the field was rarely mentioned as a barrier by participants; however, this population with their varied careers could afford to carry low-paid work, as it was offset by other work.…”
Section: Box 5 Team Work and Boundariesmentioning
confidence: 99%
“…Charity care is difficult to quantify (11), and although current foundation (28) and federal grants (29) are targeting this important source of care for the uninsured, recent work suggests that the provision of charity care is threatened by the penetration of managed care (30).…”
Section: Other Quality Of Care Measuresmentioning
confidence: 99%
“…These results concur with previous studies that show positive perceptions towards volunteering by US physicians, 10,15 as well a commitment of physicians to social justice and the mission of helping underserved populations. 18,[23][24][25] The physicians in this study reported feeling appreciated at their safety-net clinics, which has been shown to be associated with resilience in community clinics.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] A nationwide study of volunteer physicians in community clinics in 2000 revealed many barriers to volunteering at safety-net clinics, including administrative burdens; a lack of supplies, equipment, and medical follow-up at the clinics; a lack of social services for patients; patient noncompliance; insufficient time to volunteer; and concerns about malpractice insurance. [13][14][15] The resulting deficiency in volunteer physicians means that recruitment and retention of volunteers is a pressing concern in such clinics. The problems above are not unique to volunteers in safety-net clinics.…”
Section: Introductionmentioning
confidence: 99%